Eugenia uniflora and Syzygium samarangense extracts exhibit anti-trypanosomal activity: evidence from in-silico molecular modelling, in vitro, and in vivo studies - Abdel-Fattah, Mohamed; Ibrahim, Mohammed Auwal; Abdullahi, Hadiza Lawal; Aminu, Raphael; Saad, Saad Bello; Krstin, Sonja; Wink, Michael; Sobeh, Mansour (Biomedicine & pharmacotherapy, 2021)
The parasite Trypanosoma brucei is the main cause of the sleeping sickness threatening millions of populations in many African countries. The parasitic infection is currently managed by some synthetic medications, most of them suffer limited activity spectrum and/or serious adverse effects. Some studies have pointed out the promising therapeutic potential of the plant extracts rich in polyphenols to curb down parasitic infections caused by T. brucei and other trypanosomes. In this work, the main components dominating Eugenia uniflora and Syzygium samarangense plant extracts were virtually screened, through docking, as inhibitors of seven T. brucei enzymes validated as potential drug targets. The in vitro and in vivo anti-T. brucei activities of the extracts in two treatment doses were evaluated. Moreover, the extract effects on the packed cell volume level, liver, and kidney functions were assessed. Five compounds showed strong docking and minimal binding energy to five target enzymes simultaneously and three other compounds were able to bind strongly to at least four of the target enzymes. These compounds represent lead hits to develop novel trypanocidal agents of natural origin. Both extracts showed moderate in vitro anti-trypanosomal activity. Infected animal groups treated over 5 days with the studied extracts showed an appreciable in vivo anti-trypanosomal activity and ameliorated in a dose dependent manner the anaemia, liver, and kidney damages induced by the infection. In conclusion, Eugenia uniflora and Syzygium samarangense could serve as appealing sources to treat trypanosomes infections.